(untitled) (Physical Culture and Sport: Scientific Perspective, 2022)
The article explores the pedagogical paradigm formulated by M. M. Darmanskyi in the context of shaping Christian values in educators and their impact on personal development through the transformation of pedagogical and managerial experience. The pedagogical paradigm is interpreted as a set of theoretical and methodological approaches that define the education system embodied in science and practice. Based on the study of scientific works and practical activities of M. M. Darmanskyi, it can be concluded that an educator can become a spiritually elevated individual if they understand their professional mission and possess spiritual potential. The article emphasizes the importance of Christian values in pedagogical practice, which contribute to the formation of individuals with altruistic qualities, reflection, tolerance, and so on. The analysis of M. M. Darmanskyi’s scientific and practical research confirms that upbringing and education are the main factors in personal development, and educators should play a leading role in shaping Christian values through their own behavior. The article highlights the need for the concretization of Christian values in the educational process and the role of the educator in this process. It is noted that the preparation of educators should be based on the integration of fundamental, specialized, and psycho-pedagogical training, and the principles of such training should include the unity of philosophy and education, as well as multiculturalism.